A theoretical approach to the internationalization process of MNEs in the food industry in Colombia (2010)
The purpose of this paper is to present how the Multinational Enterprises (MNEs) are preparing for the internationalization in Colombia. According to a study developed through three of the most important Multinational Enterprises from Colombia with international presence in several countries, we determine if the internationalization process of these firms is always the same instead of developing different strategies under complex environments not only for its firm but also for the market and its core business. Beginning with a review of the theory related with the internationalization process since several points of view and applying some surveys in these firms, we try to identify what it is the route for these firms to enter in markets abroad. Consequently, we try to identify the strategy and establishing which one is the pattern that these firms follows in order to enter in foreign markets and how they can be affected by it in the food industry in Colombia.